Sulfate activation of wheat straw ash to enhance the properties of high-performance concrete with recycled aggregates and waste tire steel fibers. - Fadi Althoey; Osama Zaid; Khaled Mohamed Elhadi (PLoS ONE)
A sustainable alternative to conventional concrete involves using recycled aggregates (RA) instead of natural aggregates (NA) and incorporating wheat straw ash (WSA) as a partial replacement for Portland cement. The demand for high-performance concrete (HPC) is rising due to the need for architecturally complex structures and long-span bridges, but HPC's low ductility necessitates reinforcement. Waste tire steel fibers (WTSFs) are gaining popularity for their tensile strength. However, WSA-RA concrete's low early strength is a challenge. Chemical activators like sodium sulfate can enhance early-age strength. This study evaluated the durability and strength of fiber-reinforced concrete with both inactivated and activated WSA. Tests included compressive strength, indirect tensile strength, modulus of rupture (MOR), acid attack resistance, chloride penetration, sorptivity, and water absorption. Activated WSA-RA concrete showed significantly improved early strength. The mixture with 30% RA, 40% WSA, WTSFs, and activator exhibited the highest strength at 90 days. At 60% RA content, activated concrete with 40% WSA and 2.5% WTSFs outperformed the control. Durability was enhanced with a 14-17% reduction in water absorption and sorptivity and a 25.2% decrease in chloride penetration. Acid resistance improved by 26%. X-ray diffraction (XRD) confirmed these findings with elevated hydration product peaks. This study demonstrates that chemical activation of WSA optimizes the engineering properties of WSA-modified HPC with WTSFs and RA, providing a sustainable solution to their challenges.